Culture and Legal Policy Punctuation in the Supreme Court's Gender Discrimination Cases. Issue 4 (November 2014) - Robinson, Rob
<x xml:space="preserve">Abstract</x> For the most part, punctuated equilibrium scholarship has ignored the legal policy change generated by the Supreme Court. In this study, I address this gap though an examination of the Court's equal protection and gender cases from the 1970s. My case study here has two aims. First, I offer an adaptation of the jurisprudential regimes framework as a device for framing and identifying legal policy punctuations. After identifying Reed v. Reed (1971) as the cut point of such a regime, I then use Reed and its progeny to illustrate the promise of culture in explaining stasis and change, specifically focusing on the concepts of cultural cognition and cultural surprise.